Proteomic, metabalomic, and biochemical analysis of heat treated Valencia oranges during storage - Perotti, Valeria Elisa (2011)
Heat treatment induces defense mechanisms and triggers physiological responses that allow citrus fruit to withstand stressful conditions during storage. The aim of this paper was to identify changes in the proteome and the biochemistry of Valencia oranges (Citrus sinensis cv Valencia late) subjected to heat treatment before 0, 30 and 60 d of storage at 5 °C. Heat treatment for 48 h at 37 °C and 90% relative humidity was followed by 24 h at 20 °C. Differentially expressed proteins were detected by two-dimensional differential gel electrophoresis and identified by matrix-assisted laser desorption/ionization MS. Twenty eight different proteins in 40 spots among the 61 analyzed were identified. Functional classification showed that the main affected categories were “Cell rescue, defense, and virulence” and “Metabolism”; while 20% were found to be storage proteins with the rest related to minor categories. Activity of antioxidant enzymes was also evaluated. The most conspicuous change was an increase in superoxide dismutase in both the flavedo and juice sacs. Peroxidases increased in flavedo but decreased in sacs while alcohol dehydrogenase increased in treated flavedo, but not in sacs. Other fermentative enzymes were not affected. Metabolite content showed a higher concentration of sugars in heat treated fruit, while the main acids were slightly or not affected. These results are consistent with the development of a lower degree of fruit susceptibility to fungal pathogens, thus explaining the maintenance of postharvest quality.